Effects of coaches' transformational leadership behavior on team cohesion: the mediating role of mental toughness - Peng, Yifan; Wong, Ming Yu Claudia (Frontiers in Psychology, 2025)
The leadership behavior of coaches has always been the focus of research in the field of sports, and the effect of coache' leadership behavior on team cohesion is even more of a hot research issue. Previous studies have shown that coach leadership behaviors influence individual athlete' participation in sports, thereby affecting team cohesion. Compared with traditional leadership styles, transformational leadership behavior focuses on the interaction between coaches and athletes, so more and more scholars have begun introducing transformational leadership behavior into research related to sports coaching. Additionally, mental toughness as a psychological ability plays an important role in athletes facing challenges and adversity, and is also a factor worth studying. However, current research has not yet fully explored the relationship between coache' transformational leadership behavior, team cohesion, and mental toughness, so this may be an area worthy of further research to fill some gaps in existing research. This study was a cross-sectional study, 123 high-level athletes in colleges and universities of China completed the Transformational Leadership Questionnaire, Group Cohesion Questionnaire, and Sports Mental Toughness Questionnaire. SPSS statistical software was used to conduct descriptive, Pearson correlation, and mediation analysis of the collected questionnaire data, to verify whether mental toughness plays a mediating role between coache' transformational leadership behavior and team cohesion. The results showed that coaches' transformational leadership behavior perceived by college athletes were associated with the team cohesion and the mental toughness of athletes, mental toughness partially mediated the relationship between transformational leadership and team cohesion, with a mediating effect of 16.34%. The results provided a basis for improving the coach's leadership behavior, coaching philosophy, and promoting team cohesion.